Language learning bridge: how translation and interpreting training impacts bilingual proficiency in heritage and L2 learners - Lozano-Argüelles, Cristina; Martínez-Gómez, Aída (Frontiers in Education, 2025)
IntroductionTranslation and interpreting training offers a promising context for advancing bilingual proficiency, integrating skill development while bridging second language acquisition and translation studies. This study explores how bilingual oral proficiency develops over a semester and examines the influence of bilingual profile, learner type, and initial proficiency on language growth.MethodsTwenty-three bilingual learners—primarily heritage Spanish speakers—enrolled in a semester-long translation and interpreting program. Participants completed background questionnaires and ACTFL Oral Proficiency Interviews (OPIs) in English and Spanish at the beginning and end of the semester.ResultsOverall, there were no statistically significant gains in English or Spanish oral proficiency for either heritage or second language learners. However, students with lower initial proficiency levels demonstrated greater gains across the semester, suggesting that initial proficiency is a key factor influencing short-term language development.DiscussionThese findings highlight the complexity of bilingual development and the uneven trajectory of language growth within mixed learner groups. Translation and interpreting coursework may serve not only as professional preparation but also as a vehicle for enhancing bilingual proficiency, particularly for students at intermediate levels. Although conducted at a Hispanic-Serving Institution, the study’s implications extend to other higher education contexts serving bilingual or multilingual populations.